2005
DOI: 10.1161/01.res.0000175561.55761.69
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Involved in Adenosine Triphosphate-Induced Endothelial Cell Barrier Enhancement

Abstract: Abstract-Endothelial barrier dysfunction caused by inflammatory agonists is a frequent underlying cause of vascular leak and edema. Novel strategies to preserve barrier integrity could have profound clinical impact. Adenosine triphosphate (ATP) released from endothelial cells by shear stress and injury has been shown to protect the endothelial barrier in some settings. We have demonstrated that ATP and its nonhydrolyzed analogues enhanced barrier properties of cultured endothelial cell monolayers and caused re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 49 publications
8
89
0
Order By: Relevance
“…Although TIMAP depletion did not have a significant effect on basal TER (Fig. 4B), it markedly attenuated the effects of barrierprotective agents (S1P and ATP) (18,22) (Fig. 4D).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although TIMAP depletion did not have a significant effect on basal TER (Fig. 4B), it markedly attenuated the effects of barrierprotective agents (S1P and ATP) (18,22) (Fig. 4D).…”
Section: Discussionmentioning
confidence: 92%
“…The effects of both S1P and ATP, two barrier-protective agents (18,22), were attenuated, whereas the effects of thrombin and nocodazole, both evoking barrier dysfunction (11), were enhanced by TIMAP depletion (Fig. 4D).…”
Section: Resultsmentioning
confidence: 98%
“…A number of agonists including phospholipid products (Zhang, Magnusson et al 1997;Huang, Subbaiah et al 2005) and bioactive peptides (Garcia, Siflinger-Birnboim et al 1986;van Nieuw Amerongen, Draijer et al 1998;Petrache, Verin et al 2001;Moy, Blackwell et al 2002;Birukova, Adyshev et al 2005) increase vascular endothelial permeability, which my lead to alveolar flooding and pulmonary edema. However, much smaller number of bioactive molecules capable of enhancing endothelial barrier properties have been reported so far (Garcia, Liu et al 2001;Liu, Schaphorst et al 2002;VouretCraviari, Bourcier et al 2002;Birukov, Bochkov et al 2004;Kolosova, Mirzapoiazova et al 2005), and signaling mechanisms underlying these barrier protective effects have been a major focus of ongoing studies (Lee, Lee et al 2000;Garcia, Liu et al 2001;Vouret-Craviari, Bourcier et al 2002;Birukov, Leitinger et al 2004;Dudek, Jacobson et al 2004;Kolosova, Mirzapoiazova et al 2005;Mehta, Konstantoulaki et al 2005;Singleton, Dudek et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Little is known about processes that determine barrier enhancement or protection. Recently, it has been shown that extracellular ATP stabilizes barrier function of endothelial monolayers (15,18,21) and attenuates barrier disruption caused by thrombin (12) and reperfusion (13). Extracellular purines (adenosine, ADP, and ATP) are important signaling molecules that mediate diverse biological effects via cellsurface receptors.…”
mentioning
confidence: 99%